Association between childhood maltreatment and the clinical course of bipolar disorders: A survival analysis of mood recurrences. (4th February 2022) - Grillault Laroche, Diane; Godin, Ophélia; Belzeaux, Raoul; M'Bailara, Katia; Loftus, Joséphine; Courtet, Philippe; Dubertret, Caroline; Haffen, Emmanuel; Llorca, Pierre Michel; Olie, Emilie; Passerieux, Christine; Polosan, Mircea; et al.
Abstract: Objectives: Childhood maltreatment, also referred as childhood trauma, increases the severity of bipolar disorders (BD). Childhood maltreatment has been associated with more frequent mood recurrences, however, mostly in retrospective studies. Since scarce, further prospective studies are required to identify whether childhood maltreatment may be associated with the time to recurrence in BD. Methods: Individuals with BD (N = 2008) were assessed clinically and for childhood maltreatment at baseline, and followed up for two years. The cumulative probability of mood recurrence over time was estimated with the Turnbull's extension of the Kaplan–Meier analysis for interval‐censored data, including childhood maltreatment as a whole, and then maltreatment subtypes as predictors. Analyses were adjusted for potential confounding factors. Results: The median duration of follow‐up was 22.3 months (IQR:12.0–24.8). Univariable analyses showed associations between childhood maltreatment, in particular all types of abuses (emotional, physical, and sexual) or emotional neglect, and a shorter time to recurrence (all p < 0.001). When including potential confounders into the multivariable models, the time to mood recurrence was associated with multiple/severe childhood maltreatment (i.e., total score above the 75th percentile) (HR = 1.32 95%CI (1.11–1.57), p = 0.002), and more specifically with moderate/severe physical abuse (HR = 1.44 95%CI(1.21–1.73), p < 0.0001). Living alone, lifetime anxiety disorders, lifetime number of mood episodes, baseline depressive and (hypo)manic symptoms, and baseline use of atypical antipsychotics were also associated with the time to recurrence. Conclusions: In addition to typical predictors of mood recurrences, an exposure to multiple/severe forms of childhood maltreatment, and more specifically to moderate to severe physical abuse, may increase the risk for a mood recurrence in BD. This leads to the recommendations of more scrutiny and denser follow‐up of the individuals having been exposed to such early‐life stressors.